Pengaruh Ukuran Perusahaan, Profitabilitas, Audit Tenure, Dan Ukuran Kap Terhadap Audit Delay Pada Perusahaan Properti & Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Novita Lavina; Yeni Ismiati Sigalingging; Ronald Hasudungan Rajagukguk; Septony Benyamin Siahaan2 (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to test and analyze the influence of company size, profitability, audit tenure, and KAP size on audit delay. The population of this research is property & real estate companies listed on the Indonesia Stock Exchange in 2020-2022. By using a purposive sampling technique, a sample of 174 companies was obtained from the official website of the Indonesian Stock Exchange, namely www.idx.co.id. Next, the data was analyzed using multiple linear regression analysis methods. The analytical tool used is SPSS 25. The results of this research show that audit tenure has an effect on audit delay. Meanwhile, other variables, namely company size, profitability and KAP size, have no effect on audit delay. Meanwhile, simultaneously the results obtained showed that company size, profitability, audit tenure, and KAP size had an effect on audit delay.